Blanca Alvarado Oral History - Moon, Danelle (interviewer):::::::::
On August 24, 2006, Blanca Alvarado was interviewed by Danelle Moon (then Director of SJSU Special Collections & Archives), as part of the South Bay Second Wave Feminist Oral History Project.